Anti-Müllerian hormone as a marker of premature ovarian aging in autoimmune thyroid disease. (February 2015) - Saglam, Fatma; Onal, Eda Demir; Ersoy, Reyhan; Koca, Cemile; Ergin, Merve; Erel, Ozcan; Cakir, Bekir
Abstract There is an increased incidence of autoimmune thyroid disease (AITD) in women with infertility. We hypothesized that serum anti-Müllerian hormone (AMH) levels will be lower in premenopausal women with AITD than controls. We evaluated ovarian reserve in women with AITD (n = 85) and healthy controls (n = 80), all <40 years old. Detailed data on reproductive history were obtained. Gonadotrophins, steroids, AMH, and inhibin B levels were measured during the follicular phase. The number of pregnancies as well as live births was lower in women with AITD (p < 0.01). No difference was observed in terms of FSH, estradiol, and inhibin B. AMH levels were lower in AITD women than in controls (1.16 + 0.17 versus 1.28 + 0.25 ng/ml, mean + SD, p = 0.001). According to the multiple regression analysis, even after age adjustment, AITD was significantly and independently affected AMH levels (t = 2.674, p = 0.008). Women with AITD seem to have a diminished ovarian follicular reserve and measurement of serum AMH level has the potential to be used to predict this comorbidity.